Predicting Academic Quality based on School Culture: Mediating role of Self-system Processes in High School Students - Maryam khastan; Seyed Mahmood Mirzamani Bafghi; Beheshteh Niosha (Iranian Journal of Educational Research)
Objective: The primary objective of the ongoing study was to make predictions regarding the academic  quality by analyzing the influence of school culture, considering the mediating role of the self-system's processes of high school students. Methods: The research methodology employed in this study was applied and descriptive-correlational in term of data collection. The statistical population under scrutiny encompassed all high school students from Baharestan city in 2022, totaling 300 eligible individuals selected through the implementation of the stratified sampling technique, including male and female students from the 10th, 11th, and 12th grades. For the data gathering, the research utilized questionnaires on school culture developed by Higgins and Sade (1998), Self-System Processes Questionnaire (Gagné, 2003), and The Quality of Life Scale (QOLS). The statistical tool of Pearson's correlation coefficient was applied to examine the interrelation between the variables. Subsequently, the data was analyzed to verify the heuristics and establish the path coefficients derived from the structural equations modeling. Results: The findings indicated that there exists a direct positive correlation between school culture and its self-system processes (p<0.01, β=0.528). Moreover, it was observed that school culture exerts an impact on academic quality both directly (β=0.339, p<0.01) and indirectly (β=0.286, p<0.01) through its mediation of the self-system's processes. Additionally, the self-system's processes were found to have a direct positive influence on the academic quality (p<0.01, β=0.540). Conclusions: These results emphasize the importance of creating a conducive school environment that supports students' psychological and motivational needs to achieve higher academic quality.